Differences in Maternal Care Patterns for Toddlers with Growth Disorders and Normal Growth - Dwi Maryani, Wiwik; Paryono, Paryono; Rosalinna, Rosalinna (Poltekkes Kemenkes Surakarta, 2024)
Background: Toddler growth reflects nutritional status and health, which are greatly influenced by maternal parenting patterns in meeting children's basic needs. Inappropriate parenting patterns can cause growth disorders such as low weight and below-normal height. This study aims to determine the differences in maternal parenting patterns among toddlers with growth disorders and toddlers with normal growth in Candirejo Village, Ngawen District, Klaten Regency. Methods: This study used a comparative design with descriptive methods. The study population consisted of all mothers with toddlers aged 0–5 years, with a sample size of 70 respondents selected using purposive sampling. The research instrument was a structured questionnaire that had been tested for validity and reliability. Data analysis was performed using univariate and bivariate analysis with the Kendall Tau test. Results: The results showed that most mothers were aged 20–35 years, had a high school education, and worked as housewives. Most mothers had good parenting patterns (95.7%), and most toddlers experienced normal growth (67.1%). Statistical test results showed a significant difference between mothers' parenting patterns and toddlers' growth (p = 0.0012; α < 0.05). Conclusion: There is a difference in maternal parenting patterns and toddler growth. It is recommended that health workers increase education about the importance of proper nutritional parenting patterns and provide assistance to mothers in monitoring toddler growth and development regularly at health posts.